Tsunami and Nonlinear Waves
DOI: 10.1007/978-3-540-71256-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Runup of nonlinear asymmetric waves on a plane beach

Abstract: The problem of the long wave runup on a beach is discussed in the framework of the rigorous solutions of the nonlinear shallow-water theory. The key and novel moment here is the analysis of the runup of a certain class of asymmetric waves, the face slope steepness of which exceeds the back slope steepness. Shown is that the runup height increases when the relative face slope steepness increases whereas the rundown weakly depends on the steepness. The results partially explain why the tsunami waves with the ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0
1

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 25 publications
8
47
0
1
Order By: Relevance
“…In particular, we especially note in the context of this paper the analyses using the nonlinear shallow water equations by Didenkulova (2009), Didenkulova et al (2006Didenkulova et al ( , 2007, and Pelinovsky (2006) which demonstrate the role of initial nonlinear steepness in increasing the eventual runup height, and that by Didenkulova et al (2014) who found that this nonlinear steepness effect was enhanced when the initial wave was one of depression. However, although these models have proved valuable and insightful, they are non-dispersive and hence do not capture the effects of wavenumber dispersion as the tsunami waves develop shorter length scales in their propagation shoreward.…”
Section: Introductionmentioning
confidence: 73%
“…In particular, we especially note in the context of this paper the analyses using the nonlinear shallow water equations by Didenkulova (2009), Didenkulova et al (2006Didenkulova et al ( , 2007, and Pelinovsky (2006) which demonstrate the role of initial nonlinear steepness in increasing the eventual runup height, and that by Didenkulova et al (2014) who found that this nonlinear steepness effect was enhanced when the initial wave was one of depression. However, although these models have proved valuable and insightful, they are non-dispersive and hence do not capture the effects of wavenumber dispersion as the tsunami waves develop shorter length scales in their propagation shoreward.…”
Section: Introductionmentioning
confidence: 73%
“…In particular, studies by Didenkulova (2009), Didenkulova et al (2006Didenkulova et al ( , 2007 and Pelinovsky (2006) using the nonlinear shallow water equations have elucidated the role of initial steepness in increasing the eventual run-up height, and we especially note that Didenkulova et al (2014) found that this nonlinear steepness effect was enhanced when the initial wave was one of depression.…”
Section: Introductionmentioning
confidence: 70%
“…Second, in the deep ocean a tsunami is essentially a long water wave of relatively small amplitude and hence propagates without significant change of form at a speed ffiffiffiffiffi gh p where h is the ocean depth. In this phase, the tsunami can be either a wave of depression, or a wave of elevation, or a combination of these, see the recent assessments by Didenkulova et al (2007), Arcas and Segur (2012) and Dias et al (2014). In the third phase, the tsunami wave propagates shorewards from the deep ocean over the continental slope and shelf into shallow water.…”
Section: Introductionmentioning
confidence: 98%
“…Formally, linear theory is not valid in the vicinity of the shoreline where the wave amplitude becomes comparable with the water depth. In the case of a plane beach of a constant slope it has been demonstrated that the extreme runup characteristics can be calculated rigorously from linear shallow water theory even for the nonlinear problem [Synolakis, 1991;Didenkulova et al, 2006Didenkulova et al, , 2007.…”
Section: Wave Runup Along a Convex Beachmentioning
confidence: 99%
“…The solution of the nonlinear problem strongly depends on the initial waveshape. Various shapes of the periodic incident wave trains such as the sine wave [Kaistrenko et al, 1991;Madsen and Fuhrman, 2007], cnoidal wave [Synolakis, 1991] and nonlinear deformed periodic waves [Didenkulova et al, 2006[Didenkulova et al, , 2007 have been analyzed in the literature. The relevant analysis has been also performed for a variety of solitary waves and single pulses such as soliton [Pedersen and Gjevik, 1983;Synolakis, 1987;Kânoglu, 2004], sine pulse , Lorentz pulse [Pelinovsky and Mazova, 1992], Gaussian pulse [Carrier et al, 2003;Kânoglu and Synolakis, 2006], N waves [Tadepalli and Synolakis, 1994], and ''characterized tsunami waves'' [Tinti and Tonini, 2005].…”
Section: Introductionmentioning
confidence: 99%